2020
DOI: 10.1093/mnras/staa586
|View full text |Cite
|
Sign up to set email alerts
|

High-mass X-ray binaries in nearby metal-poor galaxies: on the contribution to nebular He ii emission

Abstract: Despite significant progress both observationally and theoretically, the origin of highionization nebular He ii emission in galaxies dominated by stellar photoionization remains unclear. Accretion-powered radiation from high-mass X-ray binaries (HMXBs) is still one of the leading proposed explanations for the missing He + -ionizing photons, but this scenario has yet to be conclusively tested. In this paper, we present nebular line predictions from a grid of photoionization models with input SEDs containing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 129 publications
(200 reference statements)
6
90
0
Order By: Relevance
“…Our findings are comparable to what was reported by Senchyna et al (2020), who found no strong correlation between L X /SFR and He II /Hβ ratios for a small sample of nearby galaxies either, leading them to conclude that high-mass XRBs are not the dominant sources of He II ionizing photon production. However, our results appear to be inconsistent with the findings of Lebouteiller et al (2017), Schaerer et al (2019), andHeap, Hubeny &Lanz (2019), who reported that contribution from XRBs in the well-studied metal-poor galaxy in the local Universe, I Zw 18, can account for the nebular He II (λ4686) seen in its spectrum.…”
Section: No Evidence Of Enhanced Xrb Contribution In He II Emitterssupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are comparable to what was reported by Senchyna et al (2020), who found no strong correlation between L X /SFR and He II /Hβ ratios for a small sample of nearby galaxies either, leading them to conclude that high-mass XRBs are not the dominant sources of He II ionizing photon production. However, our results appear to be inconsistent with the findings of Lebouteiller et al (2017), Schaerer et al (2019), andHeap, Hubeny &Lanz (2019), who reported that contribution from XRBs in the well-studied metal-poor galaxy in the local Universe, I Zw 18, can account for the nebular He II (λ4686) seen in its spectrum.…”
Section: No Evidence Of Enhanced Xrb Contribution In He II Emitterssupporting
confidence: 90%
“…In the local Universe (z ∼ 0), the He II λ4868 line is often seen in the spectra of low-mass star-forming galaxies and almost all of them are metal-poor (Garnett et al 1991;Guseva, Izotov & Thuan 2000;Izotov & Thuan 2004;Shirazi & Brinchmann 2012;Kehrig et al 2015Kehrig et al , 2018Berg et al 2016;Senchyna et al 2017). Rest-frame UV observations of some of these z ∼ 0 metal-poor galaxies have revealed the presence of both He II λ1640 as well as C IV λ1540 emission lines (Berg et al 2019;Senchyna et al 2020), reinforcing the idea of high ionization due to massive, metal-poor stars. The samples of He II emitting galaxies at high redshifts have increased too, primarily using lensing (Patrício et al 2016;Berg et al 2018) and large-area spectroscopic surveys (Cassata et al 2013;Nanayakkara et al 2019;Saxena et al 2020), leading to detections of He II emitting galaxies out to z ∼ 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Binaries (for example, as implemented in the BPASS models) have in some cases relieved part of the tension (Steidel et al 2016), but they are often not enough. It has therefore been proposed and debated that the inclusion of X-ray binaries (Schaerer et al 2019;Senchyna et al 2020) or energetic shocks (Allen et al 2008;Senchyna et al 2017;Plat et al 2019) could provide means for reproducing the observed He ii fluxes and other lines produced by high-energy ionizing photons like N v and C iv within photoionization model frameworks.…”
Section: Physical Parameter Inference From Photoionization Modelsmentioning
confidence: 99%
“…Examples are local low-metallicity dwarf galaxies (e.g. Kehrig et al 2015Kehrig et al , 2018Senchyna et al 2020) Mechtley et al 2016;Villforth et al 2017;Marian et al 2019), it is still a potential channel for coordinated galaxy and black hole growth as AGN luminosity, star formation, and gas content seem to be linked (e.g. Rosario et al 2013;Husemann et al 2017;Zhuang et al 2021).…”
Section: The Origin Of He II λ1640 Emission In Jil2mentioning
confidence: 99%